Effect of SYTL3-SLC22A3 Variants, Their Haplotypes, and G × E Interactions on Serum Lipid Levels and the Risk of Coronary Artery Disease and Ischaemic Stroke - Zheng, Peng-Fei; Yin, Rui-Xing; Cao, Xiao-Li; Chen, Wu-Xian; Wu, Jin-Zhen; Huang, Feng (Frontiers in Cardiovascular Medicine, 2021)
Background: The current study aimed to investigate the effects of synaptotagmin-like 3 (SYTL3) and solute carrier family 22 member 3 (SLC22A3) single nucleotide polymorphisms (SNPs) and gene-environment (G × E) interactions on blood lipid levels as well as the risk of coronary artery disease (CAD) and ischaemic stroke (IS) in the Southern Chinese Han population. Methods: The genetic makeup of 6 SYTL3-SLC22A3 SNPs in 2269 unrelated participants (controls, 755; CAD, 758 and IS, 756) of Chinese Han ethnicity was detected by the next-generation sequencing techniques. Results: The allele and genotype frequencies of the SYTL3 rs2129209 and SLC22A3 rs539298 SNPs were significantly different between the case and control groups. The SLC22A3 rs539298 SNP was correlated with total cholesterol (TC) levels in controls, the rs539298G allele carriers maintained lower TC levels than the rs539298G allele non-carriers. At the same time, the SLC22A3 rs539298 SNP interacted with alcohol consumption would reduce the risk of CAD and IS. The SYTL3-SLC22A3 A-C-A-A-A-A, G-T-C-G-C-A and A-T-A-A-C-A haplotypes increased and the A-C-A-A-C-G haplotype reduced the risk of CAD, whereas the SYTL3-SLC22A3 A-C-A-A-A-A, G-T-C-G-A-G and A-T-A-A-C-A haplotypes increased and the A-C-A-A-A-G and A-C-A-A-C-G haplotypes reduced the risk of IS. In addition, several SNPs interacted with alcohol consumption, body mass index ≥ 24 kg/m2 and cigarette smoking to affect serum lipid parameters such as triglyceride, high-density lipoprotein cholesterol, TC, and apolipoprotein A1 levels. Conclusions: Several SYTL3-SLC22A3 variants, especially the rs539298 SNP, several haplotypes, and G × E interactions, were related to blood lipid parameters and the risk of CAD and IS in the Southern Chinese Han population.